(untitled) (Global Journal of Human-Social Science, 2023)
The aim of this paper is mainly to develop connections among three areas teacher education ethics and digital game studies The common thread among these three areas in this study is the idea of unpredictability It is well known that a great number of digital games work around situations of decision making Most of these situations imply moral and or ethical consequences Also although decision making is highly dependent on real and virtual past experience game players are usually exposed to unpredictable situations turning the decision making process more complex Likewise teachers are often faced with unexpected situations in the classroom that go beyond their area of expertise These situations also involve decision making sometimes with ethical implications The aim of this paper is mainly to develop connections among three areas teacher education ethics and digital game studies The common thread among these three areas in this study is the idea of unpredictability It is well known that a great number of digital games work around situations of decision making Most of these situations imply moral and or ethical consequences Also although decision making is highly dependent on real and virtual past experience game players are usually exposed to unpredictable situations turning the decision making process more complex Likewise teachers are often faced with unexpected situations in the classroom that go beyond their area of expertise These situations also involve decision making sometimes with ethical implications